INVESTASI ASING DI ACEH SETELAH BERLAKU UU NO. 11 TAHUN 2006 - Maryati B (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2017)
The problems associated with conducting research are the extent to which Aceh needs foreign investment in developing its region. The most important question is whether the foreign investment opportunities that exist in Law No. 11 of 2006 can be implemented as desired by the parties. It is also questionable what are the constraints of foreign investment activities in Aceh after the implementation of the Act.This writing uses qualitative descriptive analytical method with emphasis on library research in order to obtain data, in addition also using field research as primary data.The results of the study can be summarized that the main foreign investment opportunities are the existence of peace and security so that all parties including foreign investors are protected from security disturbances. Law Number 11 Year 2006 provides a great opportunity for Aceh to bring in foreign investors, but the Aceh Government does not fully use the opportunity because of a clause limiting the controversial authority with the given authority, which is to comply with prevailing norms, standards and procedures nationally. Constraints impeding foreign investment in Aceh after peace and the realization of security are rules that make investors and operators unimpeded, among others, due to the norms, standards and procedures imposed for foreign investment activities in Aceh as serious obstacles that need to be solved.